Impacts of Financial Integration in the Asia Economic Community on Competitiveness of the Commercial Banks in Vietnam - Nhung, Nguyen Cam (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 34 No 4, 2018)
This paper assesses the impacts of financial integration in the Asia Economic Community (AEC) on the capacity of finance and provision of financial services of Vietnamese commercial banks. In recent years, Vietnamese commercial banks have achieved some successes as reflected in the growth indicators of operation scales, charter capital and total assets. However, under the pressure of integration, the capital adequacy ratio (CAR) fell slightly in 2016 resulting from the applying of the CAR calculation method to commercial banks in accordance with the new regulations towards step by step approaching international standards. Compared to other countries in the AEC, the capacity of finance and provision of financial services of the Vietnamese commercial banks remains low. As a result, it is necessary to carry out synchronous and drastic measures in the coming time to enhance the competitiveness of the Vietnamese commercial banks.